In vitro, in vivo and in silico antiulcer activity of ferulic acid - Ratika Umre; Aditya Ganeshpurkar; Ankit Ganeshpurkar; Stuti Pandey; Vikas Pandey; Abhishek Shrivastava; Nazneen Dubey (SpringerOpen, 2018)
Phytochemicals encompass a wide and diverse range of products and processes. Ferulic acid, a phenolic compound, is extensively found in plants. Various studies on ferulic acid have been documented. In different experimental models, ferulic acid has shown antidiabetic, hepatoprotective, anticancer, anti-apoptotic and antiaging properties. Present work was designed to evaluate the antiulcer activity of alcoholic extract of ferulic acid. As per previous studies, ferulic acid in the dose of 10, 20, and 40 mg/kg of body weight was used in the study. In the present study, the ferulic was tested for antiulcer activity against pyloric ligation model, ethanol induced ulcers, aspirin induced ulcers and histamine induced ulcers. In vitro and in silico activity against gastric H+-K+ATPase enzyme was also studied. Ferulic acid inhibited gastric acid secretion as evident by reduction in ulcer index and lipid peroxidation, Treatment with ferulic acid caused increment in gartric pH, total acidity and free acidity. In vitro and in silico activity against gastric H+-K+ATPase enzyme confirmed inhibitory effect of ferulic acid over this enzyme. From these studies, it is established ferulic acid has ulcer healing property as revealed by in vivo, in silico and in vitro studies. Therefore, the present study confirms anti ulcer potential of ferulic acid. Keywords: Cytoprotective, Gastric lesions, Polyphenols, Docking